2019
DOI: 10.1155/2019/5459427
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Splenectomy on the Reversal of Cirrhosis: a Prospective Study

Abstract: Background. Studies have demonstrated that liver fibrosis can be reversed by medication treatments. After splenectomy, cirrhosis patients have short-term changes in several serum markers for cirrhosis and liver stiffness. Aims. To investigate the effect of splenectomy on the severity of cirrhosis. Methods. A total of 62 patients with cirrhosis and portal hypertension receiving splenectomy from December 2014 to July 2017 were enrolled. The degree of cirrhosis was preoperatively and postoperatively evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Tanabe et al demonstrated that the migration of Th2dominant splenic lymphocytes induces liver fibrosis by shifting the cytokine balance toward Th2 dominance [41]. Plenty of human studies also showed potential and significant effect of splenectomy in respect to the reversal of cirrhosis [42][43][44]. At one-year follow-up after splenectomy, Yamamoto at al.…”
Section: Discussionmentioning
confidence: 99%
“…Tanabe et al demonstrated that the migration of Th2dominant splenic lymphocytes induces liver fibrosis by shifting the cytokine balance toward Th2 dominance [41]. Plenty of human studies also showed potential and significant effect of splenectomy in respect to the reversal of cirrhosis [42][43][44]. At one-year follow-up after splenectomy, Yamamoto at al.…”
Section: Discussionmentioning
confidence: 99%
“…Microstructural-level animal experiments further demonstrated that splenectomy could effectively alleviate liver brosis in cirrhotic mice [19]. Additionally, Zeng et al reported that splenectomy could signi cantly decrease serum brosis indicators among patients with cirrhosis [20]. Various pathophysiological mechanisms may be involved in this process, wherein splenectomy plays a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that splenectomy effectively decreases portal pressure and corrects hypersplenism in patients with cirrhosis[ 83 , 84 ]. Since the progression of cirrhosis may result in a parallel increase in portal pressure, it would be worth investigating whether a reduction in portal pressure, after splenectomy, contributes to decreased lymph formation and decreased overload of the lymphatic system.…”
Section: Therapeutic Perspectivementioning
confidence: 99%